To solve the expression \( 3^7 \cdot 3^{-9} \) using the properties of exponents, we can apply the rule that states:
\[ a^m \cdot a^n = a^{m+n} \]
Applying this rule to our expression:
\[ 3^7 \cdot 3^{-9} = 3^{7 + (-9)} = 3^{-2} \]
Next, we can convert \( 3^{-2} \) to have a positive exponent by using the property of exponents that states:
\[ a^{-n} = \frac{1}{a^n} \]
Thus:
\[ 3^{-2} = \frac{1}{3^2} \]
Now we can evaluate \( 3^2 \):
\[ 3^2 = 9 \]
So we have:
\[ 3^{-2} = \frac{1}{9} \]
Therefore, the equivalent expression with only positive exponents is:
\[ 3^7 \cdot 3^{-9} = \frac{1}{9} \]
Final answer: \( \frac{1}{9} \)